Strategi Komunikasi Pemasaran Produk Pakaian Bekas pada Toko Hayko.Sb dalam Meningkatkan Penjualan di Manokwari - Sandrina Sandrina; Iman Sumarlan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to examine the marketing communication strategies implemented by Hayko.SB Store in enhancing sales performance and strengthening its competitiveness within the thrift shop industry in Manokwari. The research adopts an Integrated Marketing Communication (IMC) framework, employing the marketing mix dimensions of product, price, place, and promotion. A descriptive qualitative approach is applied through in-depth interviews, observations, and documentation. The findings indicate that discount-based promotions, the strategic use of Instagram, and participation in local events effectively attract consumers, particularly adolescents and young adults. The implementation of product, price, and place strategies demonstrates considerable effectiveness, as reflected in trend-oriented product quality, affordable pricing, and the integration of online and offline distribution channels. The promotional dimension remains less optimal due to the limited use of paid advertising and influencer collaborations. The study recommends optimizing integrated digital promotion strategies to enhance brand awareness and broaden market reach.